Hypercyclic operators on algebra of symmetric analytic functions on $\ell_p$ - Mozhyrovska, Z.G. (Carpathian Mathematical Publications, 2016)
In the paper, it is proposed a method of construction of hypercyclic composition operators on $H(\mathbb{C}^n)$ using polynomial automorphisms of $\mathbb{C}^n$ and symmetric analytic functions on $\ell_p.$ In particular, we show that an "symmetric translation" operator is hypercyclic on a Frechet algebra of symmetric entire functions on $\ell_p$ which are bounded on bounded subsets.